The employers' assessment of the work performance of trained physically disabled workers in open employment - Villegas, Susan B.
This study was conducted to determine employer's assessment of the work performance of trained physically disabled employees in open employment from July-December 1979. The evaluation criteria involved measuring the frequency of uninterrupted absence, work accident and production output or efficiency. 38 establishments participated in the study. These were categorized into: Community, Social and Personal Services, 47 ; Manufacturing, 29 ; Wholesale and Retail Trade, 11 and others (financing, accounting and power generating institutions), 13 . Of the total workforce of 16,575, 326 (2 ) were physically disabled. They were classified into: deaf-mute - 204 (62 ), blind - 26 (8 ), orthopedic cases - 94 (29 ) and others (cleft lip/palate) - 2 (1 ). Majority (94 ) of the disabled workers were permanently employed while the remaining 6 were either temporary or casual eployees. The mean age and length of service of the disabled workers were 35 years and 6.2 years, respectively. The disabled workers were employed as: service workers, 55 ; production and related workers, 22 ; clerical and related workers, 10 ; professional, technical and related workers and sales workers, 9 ; administrative, executive and managerial workers, 4 . All the disabled workers underwent some form of training either from a government or private institution, on-the-job training or both. 1/3 (34 ) of the 276 disabled workers did not incur any absence. For those with absences, they had a mean of 2 episodes of uninterrupted absence with an average duration of 6 days per episode. The 3 most common reasons for their absences were illness, extreme weather condition (typhoon/storm) and family problems. Except for 1 , the disabled workers were not involved in any work accident. The exception was due to an unsafe position/posture and being bumped by another employee.